2013
DOI: 10.4236/oji.2013.33012
|View full text |Cite
|
Sign up to set email alerts
|

Total IgA and IgA reactivity to antigen I/II epitopes in HLA-DRB1*04 positive subjects

Abstract: Bacterial adherence to the acquired dental pellicle, important in dental caries (caries), is mediated by receptor-adhesins such as salivary agglutinin binding to Streptococcus mutans antigen I/II (I/II). Ten selected I/II epitopes were chosen to determine their reactivity to human salivary IgA. Previous studies suggested that a specific HLA biomarker group (HLA-DRB1*04) may have differential influence of immune responses to I/II. However, it was not known whether secretory IgA (SIgA) responses to the selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
4
1
2
Order By: Relevance
“…Moreover, Bagherian et al 21 found that the allele frequency of HLA-DRB1*04 was 10-fold greater in children with caries than in caries-free children, which suggested that the HLA-DRB1*04 allele might confer susceptibility to caries. Valarini et al 22 performed a comparative analysis of 15-to 19-year-old students with or without caries; their findings confirmed a close relationship between HLA genes and caries. In particular, the HLA-DQ gene was more frequently found in students with caries.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, Bagherian et al 21 found that the allele frequency of HLA-DRB1*04 was 10-fold greater in children with caries than in caries-free children, which suggested that the HLA-DRB1*04 allele might confer susceptibility to caries. Valarini et al 22 performed a comparative analysis of 15-to 19-year-old students with or without caries; their findings confirmed a close relationship between HLA genes and caries. In particular, the HLA-DQ gene was more frequently found in students with caries.…”
Section: Discussionmentioning
confidence: 84%
“…Valarini et al. 22 performed a comparative analysis of 15- to 19-year-old students with or without caries; their findings confirmed a close relationship between HLA genes and caries. In particular, the HLA-DQ gene was more frequently found in students with caries.…”
Section: Discussionmentioning
confidence: 84%
“…Sekretori IgA (SIgA) saliva dapat berikatan secara spesifik dengan epitop dari bagian antigen I/II S. mutans, sehingga bakteri tidak dapat berikatan dengan pelikel saliva dan S. mutans tidak akan berkolonisasi pada permukaan gigi. 3,4,6,[7][8][9] Penulisan artikel ini bertujuan untuk mengetahui peran SIgA dalam meningkatkan pertahanan mukosa mulut terhadap bakteri patogen Streptococcus mutans.…”
Section: Pendahuluanunclassified
“…Famili protein ini direpresentasikan oleh SpaP, SspA atau SspB yang terdapat pada permukaan S. mutans (Gambar 2). [3][4][5]9 Selain itu, Streptococcus mutans dapat memproduksi asam dari substrat karbohidrat (glukosa dan fruktosa) yang dikenal dengan sifat asidogenik. Di samping itu sifat asidurik, memungkinkan bakteri ini dapat bertahan dalam kondisi pH rendah (pH 3,0) yang menyebabkan demineralisasi pada email, sehingga meningkatkan potensi kariogenik.…”
Section: Glucans Binding Of Proteins (Gbp) Merupakan Komponen Virulenunclassified
“…In a Caucasian population, a higher dose of streptococcal antigen was required to release T‐helper activity in DR4 positive individuals compared to cells carrying the HLA DR1,2,3,6 cross reactive groups . McCarlie et al . reported HLA‐DR4 positive subjects exhibited reduced reactivity to S. mutans antigen I/II, lower specific secretory immunoglobulin A activity/total Immunoglobulin A and a lower specific reactivity to whole cell S. mutans UA159, suggesting a potential link between HLA‐DR04 and caries.…”
Section: Introductionmentioning
confidence: 99%